Benefiting from Diversity: How Groups' Coordinating Mechanisms Affect Leadership Opportunities for Marginalized Individuals. (25th March 2018) - Packer, Dominic J.; Miners, Christopher T. H.; Ungson, Nick D.
Abstract: Research suggests that prototypical group members often exert stronger social influence and thus have greater leadership opportunities relative to members of marginalized or underrepresented social categories. This article offers a new model for understanding and promoting leadership diversity by focusing on the mechanisms by which a group or organization coordinates behavior among its members. We predict that means‐focused groups (in which social norms drive coordination) are likely to suppress influence among non‐prototypic members, whereas ends‐focused groups (in which shared goals drive coordination) are more likely to allow for leadership from a diverse set of members. The primary mechanism by which a group coordinates its members—social norms versus shared goals—is thus expected to serve as a critical moderator affecting the likelihood that group‐level diversity will translate into inclusion, innovation, performance, and prosperity. Implications of the model for policy and practice, particularly in organizational settings, are discussed.